Kant, Applied A Conversation with Onora O'Neill. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Onora O'Neill, Emeritus Professor of Philosophy at the University of Cambridge and a crossbench member of the House of Lords. After intriguing insights into Onora O'Neill's path to becoming a Kant scholar, this wide-ranging conversation explores how Kant's philosophy is relevant for many thorny issues in our contemporary social world, from human rights to patient consent to corporate transparency and more.This carefully-edited book includes an introduction, The Benefits of Struggling, and questions for discussion a.